Properties of concrete containing used engine oil - Shafiq, Nasir; Nuruddin, Muhd Fadhil; Beddu, Salmia (International Journal of Sustainable Construction Engineering and Technology, 2011)
Since last few years cement replacement materials, industrial by-products and agricultural wastes in concrete production are widely used. It imparts positive environmental effect because the waste materials are not released to the environment. It was reported that the leakage of motor oil onto concrete surfaces in old grinding units increased the resistance such concrete to freezing and thawing, it made to understand that the effect is similar to adding an air-entraining chemical admixture to the concrete. However, the hypothesis is not backed by significant research study and not reported in the available literature. This paper presents results of the experimental study conducted to investigate the effects of used engine oil on properties of fresh and hardened concrete.  With the addition of used engine oil, concrete slump was increased by 18% to 38% and air content by 26% to 58% as compare to the slump of control concrete. Porosity and oxygen permeability of concrete containing used engine oil was also reduced and the compressive strength was obtained approximately same as that of the control mix